The Rejuvenation of the Aged Central Lower Face: A Contemporary Perspective - Fedok, Fred G. (Facial Plastic Surgery, 2019)
Aging of the central face is typified by several common characteristics such as generalized volume loss, the appearance of a mental crease and marionette lines, thinning of the lips, and fixed and dynamic rhytids. These result from several processes such as atrophy of adipose and bone, changes in the support of the mandibular septum, and a loss of skin elasticity. There are many methods available for the improvement and rejuvenation of this facial anatomical area. Options include traditional surgical techniques, the application of volume and the use of laser, light, and energy-based devices. The recent application of biological interventions offers the possibility of cellular-based therapies to usher in a new era of true tissue regeneration. Optimal correction of the abnormalities may be accomplished through an understanding and identification of the causes of the observed abnormalities and targeting with the best available intervention. There are a growing number of techniques and technologies to accomplish this.
Keywords: central lower face; biologicals; platelet-rich plasma; fat transfer; marionette lines